Assessment of the impact of oil products on the development of agricultural plants - Bondar, T. O.; Bosiuk, A. S.; Nechyporenko, D. I.; Lifer, V. E.; Melnyk, I. V. (Zhytomyr Ivan Franko State University, 2025)
The study focuses on the pressing environmental challenge ofoil pollution and its detrimental effects on agroecosystems, which play a pivotal role in global food security. With the growing demands ofmodern sustainable development, industrial and transportation systems are faced with the dual challenge ofachieving economic progress while minimizing ecological harm. Among the most signifiant concerns is the contamination caused by petroleum products, which profoundly affects soil quality, plant health, and overall ecosystem stability. The article explores the toxic mechanisms ofhydrocarbons on plant development, particularly their impacts on seed germination, root elongation, and photosynthetic processes, which are essential for growth and productivity. It has been found that even low concentrations ofoil products (1–3.0 mg/kg) have a toxic effect on seed germination, root development, and physiological processes such as photosynthesis. It was found that the acidity of the soil varies depending on the degree ofoil contamination. In sample № 1, the pH = 6 indicates a rather acidic and toxic soil with iron, aluminum and manganese, which limits the yield to 50%. In sample № 2, the pH = 6.4 indicates satisfactory soil acidity. Laboratory tests confim that natural decomposition and leaching ofoil products occurred in the contaminated soil within 6 months, indicating that the soil has begun to cleanse itself through natural mechanisms. By addressing the intersection ofenvironmental sustainability, industrial activity, and agricultural productivity, this research offers valuable insights for agricultural practitioners. The scientifi novelty of the study lies in a comprehensive analysis of the impact ofpetroleum products on the growth and development ofagricultural plants, taking into account both the initial and long-term effects. The mechanisms oftoxic effects ofhydrocarbons on plant physiological processes are studied in detail. Particular attention is paid to the identifiation ofpollutionresistant plant species that can serve as bioindicators or be used for phytoremediation ofcontaminated areas.

Дослідження зосереджено на нагальній екологічній проблемі забруднення нафтопродуктами та її негативному впливі на агроекосистеми, які відіграють ключову роль у глобальній продовольчій безпеці. З огляду на зростаючі вимоги сучасного сталого розвитку промислові та транспортні системи стикаються з подвійним викликом: досягнення економічного прогресу за мінімізації екологічної шкоди. Серед найбільш значущих проблем – забруднення, спричинене нафтопродуктами, яке глибоко впливає на якість ґрунту, здоров’я рослин і загальну стабільність екосистеми. У статті досліджуються токсичні механізми впливу вуглеводнів на розвиток рослин, зокрема їхній вплив на проростання насіння, довжину коренів і фотосинтетичні процеси, які є важливими для росту та продуктивності. З’ясовано, що навіть низькі концентрації нафтопродуктів (1–3,0 мг/кг) спричиняють токсичний вплив на проростання насіння, розвиток кореневої системи та фізіологічні процеси, зокрема фотосинтез. Встановлено, що кислотність ґрунту змінюється залежно від ступеня забруднення нафтопродуктами. У зразку № 1 кислотність рН = 6 свідчить про досить кислий і токсичний ґрунт із вмістом заліза, алюмінію та марганцю, що обмежує врожайність до 50%. У зразку № 2 рН = 6,4 вказує на задовільну кислотність ґрунту. Лабораторні дослідження підтверджують, що протягом 6 місяців у забрудненому ґрунті відбувалося природне розкладання та вимивання нафтопродуктів, що свідчить про початок процесу самоочищення ґрунту через природні механізми. Вивчаючи взаємозв’язок між екологічною стійкістю, промисловою діяльністю та продуктивністю сільського господарства, це дослідження пропонує цінну інформацію для практиків сільського господарства. Наукова новизна дослідження полягає у комплексному аналізі впливу нафтопродуктів на ріст і розвиток сільськогосподарських рослин з урахуванням як початкових, так і віддалених наслідків. Детально вивчено механізми токсичної дії вуглеводнів на фізіологічні процеси рослин. Особливу увагу приділено виявленню стійких до забруднення видів рослин, які можуть слугувати біоіндикаторами або використовуватися для фіторемедіації забруднених територій.
Оцінка впливу нафтопродуктів на розвиток сільськогосподарських рослин
Keywords: oil products; sustainable development; environment; soil pollution; agroecosystems; agricultural plants; нафтопродукти; сталий розвиток; довкілля; забруднення ґрунтів; агроекосистеми; сільськогосподарські рослини